Effect of Acid Suppressants on Non–Helicobacter pylori Helicobacters Within Parietal Cells - Nakamura, Masahiko; Murasato, Futa; Øverby, Anders; Kodama, Yosuke; Michimae, Hirofumi; Sasaki, Kazuki; Flahou, Bram; Haesebrouck, Freddy; Murayama, Somay Y.; Takahashi, Shinichi; Uchida, Masayuki; Suzuki, Hidekazu; et al. (Frontiers in Pharmacology, 2022)
We investigated the effect of increased pH induced by acid suppressants on the viability of non-Helicobacter-pylori Helicobacters (NHPHs) within parietal cell intracellular canaliculi and fundic glandular lumina using immunohistochemistry, electron microscopy, quantitative PCR, urea breath tests, and bilayer culture system. Three months before the experiment, mice were infected with the NHPH H. suis and then treated with famotidine (2 mg/kg body weight [BW], once daily), lansoprazole (30 mg/kg BW, once daily), or vonoprazan (20 mg/kg BW, once daily) for three days. Immunohistochemical studies using the TUNEL method, quantitative PCR analysis, and urea breath tests were performed. PCR analysis showed a decrease in NHPH quantity after vonoprazan treatment. Urea breath tests revealed a significant decrease in NHPH urease activity after vonoprazan, lansoprazole, and famotidine treatments for 3 days; however, 4 days after the treatment, urease activity reversed to the pretreatment level for each treatment group. Electron microscopy revealed an increase in damaged NHPH after vonoprazan treatment. The TUNEL method revealed apoptotic NHPH within parietal cells after vonoprazan treatment. The bilayer culture results demonstrated that NHPH moved more quickly at a pH of 4.0, than at a pH of 3.0, 5.0, and 6.5, and electron microscopy revealed a change from the spiral form to the coccoid form under near-neutral pH conditions. We thus propose that acid suppressants, especially vonoprazan, induce NHPH damage by altering pH.